LQ45 Stock Price Valuation Analysis Using Price to Book Value (PBV) and Price Earning Ratio (PER) Variables from 2016-2020 - Davin Surjanto; Totok Sugiharto (Institute of Computer Science (IOCS), 2021)
The research was conducted with the aim of knowing the effect of the stock valuation method on the company's stock price for the last five years. The sample used is consistent companies listed in the LQ45 index from 2016 – 2020 with quarterly data. Data analysis was performed using multiple linear regression because there is 1 dependent variable (stock price) and 2 independent variables (price to book value (PBV) and price earning ratio (PER)). The results of the study stated that the stock price was most influenced by the price to book value (PBV) in this study, while the price earning ratio (PER) did not affect the stock price in this study. However, based on the results of simultaneous testing, it is found that price to book value (PBV) and price earning ratio (PER) simultaneously affect stock prices.